Aerobic Poise of Marine Fish in Relation to Habitat and Lifestyle - Ludi Parwadani Aji (Faculty of Mathtmatics and Natural Sciences, 2011)
Fish from different species have different way to deal with their lifestyle and habitat. From four species that have been researched, Pseudocaranx dentex and Scomberomorus munroi have higher proportion of red muscle, higher relative gill and higher ventricular mass also their muscle have higher buffering capacity than Lethrinus miniatus and Lutjanus erythropterus. It also has been found that white muscle has better ability to handle acid than red muscle. The red muscle are involved in the aerobic slow swimming, while the white muscle have role in faster or burst swimming (anaerobic energy pathway). Therefore, Lethrinus miniatus and Lutjanus erythropterus are less active fish than Pseudocaranx dentex and Scomberomorus munroi.